2018
DOI: 10.3892/etm.2018.5937
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoric and carboxylic methacrylate esters as bonding agents in self-adhesive resin cements

Abstract: The aim of the present study was to investigate the effect of pH and phosphoric ester structure (phosphonate or phosphate) on the bond strength of different dental restorative materials. The following three self-adhesive resin cements were used in the present study: RelyX Unicem, Maxcem and Multilink Sprint The pH of each cement was measured using a pH meter. The cements were used to attach a variety of restorative materials to human dentin and the bond strength was measured by assessing shear strength using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
3
0
1
Order By: Relevance
“…Several previous studies also reported that resin cement or primers containing MDP could increase the bond strength by approximately 8 to 72 MPa on 3Y-TZP [16,18,19,22,23] and translucent zirconia [40,41]. Phosphoric methacrylate ester has also been reported to increase the bond strength of 3Y-TZP [24,25]. The results of this study showed that the shear bond strength of the primer containing MDP and the adhesive containing phosphoric methacrylate ester showed no significant differences, which was similar to the results of previous studies [37,43].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Several previous studies also reported that resin cement or primers containing MDP could increase the bond strength by approximately 8 to 72 MPa on 3Y-TZP [16,18,19,22,23] and translucent zirconia [40,41]. Phosphoric methacrylate ester has also been reported to increase the bond strength of 3Y-TZP [24,25]. The results of this study showed that the shear bond strength of the primer containing MDP and the adhesive containing phosphoric methacrylate ester showed no significant differences, which was similar to the results of previous studies [37,43].…”
Section: Discussionmentioning
confidence: 86%
“…This procedure should be performed to obtain durable and effective bonds [19,20] which are comparable with the bonding in metal alloys [21]. Various kinds of phosphate monomers have been included in resin cements and primers, including 10-methacryloyloxydecyl dihydrogen phosphate (MDP), phosphate methacrylate ester, glycerol phosphate dimethacrylate (GPDM), dipentaerythritol penta-acrylate monophosphate (PENTA), and phosphoric acid acrylate, all of which contribute to the enhancement of bond strength of zirconia [16,18,19,[22][23][24][25]. Previous studies have reported shear bond strengths of zirconia to composite resins ranging from 2 to 25 MPa [20,24].…”
Section: Introductionmentioning
confidence: 99%
“…From our experiment, the highest percentages of absorption were recorded for the sample 4 (with the lowest organic matrix concentration) and the sample 3. For the sample 4, the acidic nature of the phosphorylated methacrylate can cause erosion of surfaces of samples tested by us due to hydrolysis of the methacrylate ester bond in water [15]. The sample 1 showed a low percentage of water absorption and the lowest percentage of saliva absorption compared to the other investigated materials.…”
Section: Determination Of Water and Artificial Saliva Sorption For Studied Compositesmentioning
confidence: 90%
“…O termo cimento resinoso tem sido usado para descrever materiais de cimentação baseados em polímeros (LIU et al, 2018).…”
Section: Revisão De Literaturaunclassified